Evaluating the Significance of Delaying Intravenous Lipid Therapy During the First Week of Hospitalization in the Intensive Care Unit. (June 2014) - Arrazcaeta, Janet; Lemon, Stephen
Background: The American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.) and the Society of Critical Care Medicine (SCCM) published guidelines in 2009 recommending against the use of intravenous lipids for parenteral nutrition (PN) within the first week of hospitalization in critically ill patients. This grade D recommendation is controversial as it is based on the results of 2 studies that evaluated approximately 100 patients and did not evaluate glycemic control. The purpose of this study was to evaluate outcomes associated with the receipt of lipids within the first week in the intensive care unit (ICU) compared with withholding lipids. Methods : This retrospective study included critically ill adult patients who received PN at a large, academic medical center. This study examined the incidence of new infections with receipt of early lipids (n = 66) compared with withholding lipids in the first 7 days (n = 29). Secondary outcomes included mortality, hyperglycemia, ICU length of stay (LOS), and total LOS. Results : There was no difference between the early lipids and late lipids groups in the incidence of new infections after the initiation of PN (40.9% vs 55.2%, P = .264). Additionally, there was no difference between groups for any of the secondary outcomes. Conclusion : Withholding lipids within the first 7 days of hospitalization in the ICU was not associated with a significant reduction in infections, ICU or total LOS, or mortality. A multicenter, randomized, controlled trial is needed to further evaluate the effects of lipid administration in the critically ill.